Turkish version of a short nutrition literacy scale for young adults: cultural adaptation and validation - Koc, Mustafa Can; Yildirim, Elif; Isik, Ozkan; Aksen, Pelin; Talaghir, Laurentiu-Gabriel; Zanfir, Ciprian (Frontiers in Nutrition, 2024)
Background: Recent changes in nutrition trends may lead to health issues. In particular, the unhealthy eating habits of young adults suggest that future generations may be at risk. Therefore, the importance and necessity of nutrition literacy is becoming increasingly apparent.The purpose of this study was to create a Turkish version of a short nutrition literacy (S-NutLit-Tr) scale for young adults developed by Vrinten et al. (1).Methods: This research involved 115 young adults from Istanbul Gelişim University, who were selected through convenience sampling, a non-probability sampling method. After the original S-NutLit scale was translated into Turkish, the validity and reliability of the determined factor structure were tested on 115 young adults. Internal consistency was examined with the Cronbach Alpha coefficient. Confirmatory factor analysis was employed to validate the two sub-scale structures. Finally, measurement invariance was tested concerning participants' gender, aiming to ascertain whether the scale captured equivalent characteristics across different groups.Results: As a result of the reliability analysis conducted with the scale of S-NutLit-Tr, the Cronbach Alpha coefficient was obtained as 0.86 for the scale of S-NutLit-Tr. Additionally, it was found to be 0.84 and 0.77 for the 'information skills' and 'expert skills' sub-scales, respectively. Accordingly, the scale of S-NutLit-Tr was found to be reliable. To examine the two sub-scale factor structures of the S-NutLit-Tr scale, fit indices were examined: χ^2/df (1.246), GFI (0.923), IFI (0.975), TLI (0.967), CFI (0.974), RMSEA (0.046) and SRMR (0.055) and it was observed that the indices were within acceptable limits. In the analysis results obtained through the multi-group confirmatory factor analysis for measurement invariance, it was observed that the ∆CFI and ∆TLI values across all indices were less than or equal to 0.01. Consequently, it was observed that the item-factor structure, factor loadings, variances, covariances, and error variances of the scale were equivalent for both male and female young adults.The study found that the scale of S-NutLit-Tr for young adults was a valid and reliable measurement tool in Turkish culture.